Senecio spp. transboundary introduction and expansion affecting cattle in Uruguay: Clinico-pathological, epidemiological and genetic survey, and experimental intoxication with Senecio oxyphyllus. (15th January 2020) - García, Juan A.; Rosas, Juan E.; García y Santos, Carmen; Streitenberger, Nicolas; Feijoo, Matías; Dutra, Fernando
Abstract: The genus Senecio is distributed worldwide, being responsible of poisoning in livestock and humans. Many species of Senecio have high invasion and expansion capacity, highly competitive with agricultural and native plant species, causing ecological damage. Particularly in Uruguay, poisoning by Senecio have grown exponentially to reach epidemic proportions. Herein we describe Seneciosis as a re-emerging and expanding epidemic disease affecting cattle, by describing clinico-pathological, epidemiological and genetic variation of species involved, as well as an experimental intoxication with Senecio oxyphyllus . For this, a study was carried out on 28 cattle farms in Eastern Uruguay, with history of seneciosis from 2010 to 2016. Plants of fifty populations of Senecio were sampled, in 2015 and 2016, for identification, analysis of alkaloids and study of genetic variation. In turn, post-mortem examination was performed in cattle of natural and an experimental case to confirm the intoxication, showing microscopic characteristic lesions (hepatomegalocytosis, diffuse fibrosis and ductal reaction). Four species of Senecio were identified: S. oxyphyllus, S. madagascariensis, S. selloi and S. brasiliensis . In the genetic study, 489 molecular markers of amplified sequence-related polymorphisms (SRAP), associated with species and pasture, were used for genetic variation analysis. There was no statistically significant association between genetic variation determined by molecular markers and population (specimens of same species collected from the same farm), botanically determined species, or geographical origin. The increase of seneciosis in cattle in the last years, the presence of species not identified to the moment with implication in the poisoning outbreaks and expansion of these plants shows that the disease is in an epidemic growing active stage. In turn, the experimental poisoning with S. oxyphyllus confirms its chronic hepatotoxic effect, being an emergent species for the region, of high distribution and toxic risk. This latter turned out the main Senecio species involved. This case of expansion of harmful plant for animal production and desirable plant species, can be useful as a model of ecopathological characterization, which is likely to occur with other toxic plants in different geographical ranges globally. Highlights: Senecio spp. plant intoxication is responsible of the most frequent plant-related poisoning in animal production. Senecio spp. have a high invasive and expansive capacity out of their geographic range being an important ecological problem. Invaders success is facilitated by high genetic variability, increasing their potential to adapt to new environments. Some Senecio spp. are considered plague, associated with cattle poisoning and deterioration of desirable native pastures. Events of appearance and expansion of Senecio species have been recorded.